Exploration Into Game-Based Learning For Young Adults - Tao, Sun (2010)
The study explores the game-based learning for young adults. Computer games are quite attractive, combining computer games and education together is highly valued by researchers. Game-based learning (GBL) refers to different kinds of software applications that use for learning. In order to develop a game-based learning application, we should follow some principle of game-based learning.